Florid osseous dysplasia. (27th June 2013) - Mohan, Ravi Prakash Sasankoti; Verma, Sankalp; Singh, Udita; Agarwal, Neha
Abstract : Florid osseous dysplasia (FOD) is the most dramatic and rare variant of the cemento-osseous lesions in which the normal cancellous bone is replaced by dense, acellular cemento-osseous tissue in a background of fibrous connective tissue. It appears to be a widespread form of periapical cemental dysplasia (PCD). No clear definition indicates that when the multiple lesions of PCD can be termed as FOD. If PCD is identified in three or four quadrants or is extensive in one jaw, then it is considered as FOD. Here, in this article, we report a case of FOD in 35-year-old woman.